Priorities in crime prevention policies across Europe - Vanhauwaert, Rosita (European crime prevention monitor, 2013)
In the European Crime Prevention Monitor 2012/2 (EUCPN, 2012b), the EUCPN Secretariat collected information from the Member States on their main priorities in the crime prevention policy/strategy in their countries. Obviously, each country has its own strategy and approach regarding crime prevention. Whereas some countries pay specific attention to certain crime types in their prevention strategy, others – like e.g., the Czech Republic, Denmark and the United Kingdom – have a broad and general preventative approach at the national level, with more room to focus on local crime prevention priorities. Overall, the crime types which were considered most in the various prevention policies are: 1. Property crimes (i.e. burglaries, theft); 2. Crimes against the person (i.e. violence, domestic violence); 3. Juvenile delinquency; 4. Drug use; and 5. Violent crime. In this third Monitor, we will have a closer look at some of these crime types which are currently prioritised by the Member States and which were identified in the previous Monitor (EUCPN, 2012b). For this, we will draw upon some of the findings of the International Crime Victimization Survey of 2005 and 2010 (ICVS), Eurostat’s Statistics in Focus 2013, the Statistical Bulletin 2013 of the European Monitoring Centre for Drug and Drug Addiction and the European School Survey Project on Alcohol and Other Drugs 2011 (ESPAD).